ETOS KERJA PROFESIONAL GURU PENDIDIKAN AGAMA KRISTEN - Hana Suparti; Ezra Tari (Regula Fidei: Jurnal Pendidikan Agama Kristen, 2019)
Here the writer conducted a study of the professional work ethic of Christian Education teachers. This study starts from the anxiety of the writer towards the conditions of the teacher's work ethic, who in actually the teachers have now lost their direction in carrying out their duties. In East Indonesia Region many teachers do not fulfill the undergraduate education qualifications. With this problem, the writer examine the professional work ethic from empirical experience. Based on investigations conducted by the writer in this article, then there are two important things that need to be learned, namely first, teachers who have standards or qualifications in teaching. Second, the availability of facilities and infrastructure that support the implementation of teaching and learning processes. Therefore, the search for the work ethic of the Christian Education teacher is related to the activities of the teacher in carrying out the task. Penulis melakukan kajian terhadap etos kerja professional guru Pendidikan Agama Kristen. Kajian ini berangkat dari kegelisahan penulis terhadap kondisi etos kerja guru, di mana para guru sekarang ini telah hilang arah dalam melaksanakan tugas. Daerah Indonesia Timur banyak guru tidak memenuhi kualifikasi pendidikan strata satu. Dengan persoalan itu maka, penulis mengupas tentang etos kerja profesional dari pengalaman empiris. Berdasarkan penyelidikan yang dilakukan oleh penulis dalam artikel ini, maka ada dua hal penting yang perlu dipelajari, yakni pertama, guru yang memeliki standar atau kualifikasi dalam mengajar. Kedua, ketersediaan sarana dan prasarana yang mendukung terlaksanya proses belaajr mengajar. Karena itu,penelusuran tentang etos kerja guru Pendidikan Agama Kristen berkaitan dengan aktivitas guru dalam melaksanakan tugas.